Derecho y arte. La epistemología del oprimido en la enseñanza del derecho desde un diálogo con el cine (Tema Central) - Córdova Vinueza, Holger Paúl (2020)
The objective of the article is to reinvent the epistemological dimensions that appear in the teaching and learning of law through the exchange of critical reasons that would be observed with the help of materials such as film histories of cases related to the application of law. For this, the discussion arose from an approach to two types of epistemology: i) that of domination and ii) that of the oppressed, in order to make visible that the law can develop a teaching and learning story in correspondence with one of they. Hence, the result and conclusion is that those who participate in these processes can attend human experiences through a dialogue with film stories to understand the dynamics of the world of law in order to raise awareness of their power structures with the intention of rethinking the life of the oppressed and give answers to them from legal education, understanding this process as a means of transforming the legal culture.